Factors affecting the function of the mitochondrial membrane permeability transition pore and their role in evaluation of calcium retention capacity values - Drahota, Zdeněk; Endlicher, René; Kučera, Otto; Rychtrmoc, David; Červinková, Zuzana (Physiological research, 2020)
Values of the calcium retention capacity (CRC) of rat liver mitochondria are highly dependent on the experimental conditions used. When increasing amounts of added calcium chloride are used (1.25-10 nmol), the values of the CRC increase 3-fold. When calcium is added in 75 s intervals, the CRC values increase by 30 % compared with 150 s interval additions. CRC values are not dependent on the calcium/protein ratio in the measured sample in our experimental design. We also show that a more detailed evaluation of the fluorescence curves can provide new information about mitochondrial permeability transition pore opening after calcium is added.
Keywords: Liver; Mitochondria, Liver; jaterní mitochondrie; Animals; Mitochondrial Membrane Transport Proteins; biologický transport; Research Design; játra; Mitochondrial Permeability Transition Pore; transportní proteiny mitochondriální membrány; mitochondriální membrány; vápník; Biological Transport; Calcium; Male; permeabilita; Permeability; krysa rodu Rattus; Mitochondrial Membranes; mužské pohlaví; zvířata; výzkumný projekt; Rats; přechodový pór mitochondriální permeability